Tortoise's Dream (An African folktale) Folktales of the world - Troughton, Joanna (Puffin Books, 1994)
Tortoise dreams of a miraculous tree, bearing all the fruits of the Earth - but who will be clever enough to find it?
Keywords: Folktales, English